A review of money laundering literature: the state of research in key areas. Issue 2 (20th March 2020) - Tiwari, Milind; Gepp, Adrian; Kumar, Kuldeep
Abstract : Purpose: The purpose of this study is to review the literature on money laundering and its related areas. The main objective is to identify any gaps in the literature and direct attention towards addressing them. Design/methodology/approach: A systematic review of the money laundering literature was conducted with an emphasis on the Pro-Quest, Scopus and Science-Direct databases. Broad research themes were identified after investigating the literature. The theme about the detection of money laundering was then further investigated. The major approaches of such detection are identified, as well as research gaps that could be addressed in future studies. Findings: The literature on money laundering can be classified into the following six broad areas: anti-money laundering framework and its effectiveness, the effect of money laundering on other fields and the economy, the role of actors and their relative importance, the magnitude of money laundering, new opportunities available for money laundering and detection of money laundering. Most studies about the detection of money laundering have focused on the use of innovative technologies, banking transactions or real estate- and trade-based money laundering. However, the literature on the detection of shell companies being explicitly used to launder funds is relatively scarce. Originality/value: This paper provides insights into an area related to money laundering where research is relatively scant. Shell companies incorporated in the UK alone were identified to be associated with laundering £80bn of stolen money between 2010 and 2014. The use of these entities to launder billions of dollars as witnessed through the laundromat schemes and several data leaks clearly indicate the need to focus on illicit financial flows through such entities.